The Occurrence of Thrombotic Complications Due to Combat Trauma Against the Background of the COVID-19 Pandemic - Gogayeva, Olena K.; Rudenko, Mykola L.; Nudchenko, Oleksandr O. (Ukrainian Journal of Cardiovascular Surgery, 2022)
An important point in the provision of highly specialized cardiac surgical care for combat trauma is determination of the optimal time, method and volume of surgical intervention, taking into account the persisting threat of infection with the SARS-COV-2 virus and associated thrombotic complications. The aim. To investigate the mechanism of development and methods of prevention of thrombotic complications resulting from combat trauma against the background of the COVID-19 pandemic. Materials and methods. We analyzed clinical case of patient R., a 37-year-old soldier with a postinfarction thrombosed aneurysm of the left ventricle. The patient underwent standard clinical and laboratory tests, electrocardiography, echocardiography, coronary angiography, computed tomography of the chest, duplex scanning of carotid arteries, arteries and veins of the upper and lower extremities. It was established that 4 months ago, during a combat mission, the service-man received a mine-explosive injury, shrapnel wounds of lower extremities, multifragmentary fracture of the right ϐibula and a gunshot wound to the right chest. The causes of post-traumatic myocardial infarction are mine-explosive injury, intramural course of the left anterior descending artery, youngage, poorly developed collaterals of coronary arteries, long-term transportation during the stages of medical evacuation and post-traumatic stress disorder. A month ago, the patient was diagnosed with COVID-19, thromboembolism of the right main branch of the pulmonary artery, for which thrombolytic therapy was performed. Follow-up computed tomography showed the signs of thromboembolism of the pulmonary arteries. Ultrasound examination revealed thromboses of upper and lower limbs. Thrombotic complications against the background of combat polytrauma are the result of hypercoagulation, acute inϐlammation with the release of proinϐlammatory cytokines and damage of the endothelium. SARS-COV-2 infection triggers a state of hypercoagulation and creates additional conditions for the occurrence of arterial and venous thrombosis. Considering the nature of the thrombotic lesions, was made a decision to postpone the cardiosurgical intervention for 3 months. Conclusions. Thrombotic complications are an urgent problem after combat trauma. COVID-19 is an additional risk factor for hypercoagulation and a reason for delaying elective cardiac surgery. Conducting an electrocardiography to the wounded, regardless of age, is crucial for timely diagnosis andtreatment of acute coronary events. It is important to initiate anticoagulant therapy after eliminating all possible sources of bleeding due to the high risk of thrombotic complications against the background of chest trauma and limb fractures.